Nonlocal effect influence on the vortex filament structure in Bose-gas - Ivashin, A.P.; Poluektov, Yu.M. (Вопросы атомной науки и техники, 2012)
Using the Gross-Pitaevskii equation (GPE), which accounts for a weak non-locality effects, we study the structure of the vortex filaments in a Bose-gas. We show that the sign of the additional terms in the generalized GPE depends on the form of the interaction potential and can be positive or negative. The generalized GPE for a single vortex is solved numerically. It is demonstrated that the non-locality can cause either an increase or a decrease of the vortex core radius. С помощью уравнения Гросса-Питаевского (ГП), учитывающего эффект слабой нелокальности, исследована структура вихревой нити в бозе-газе. Показано, что знак постоянной перед дополнительным слагаемым в обобщенном уравнении ГП зависит от вида потенциала взаимодействия и может быть как положительным, так и отрицательным. Обобщенное уравнение ГП для одиночного вихря решено численно. Показано, что учет эффекта нелокальности может приводить как к увеличению, так и к уменьшению радиуса сердцевины вихря. За допомогою рівняння Гросса-Питаєвського (ГП), яке враховує ефект малої нелокальності, досліджена структура вихру у надплинному бозе-конденсаті. Показано, що знак сталої перед додатковим доданком в узагальненому рівнянні ГП залежить від потенціалу взаємодії і може бути як додатнім, так і від'ємним. Узагальнене рівняння ГП для одинарного вихру розв'язано чисельно. Показано, що врахування ефекту нелокальності може привести як до збільшення, так і до зменшення радіусу серцевини вихру.